Giving Benson Relaxation Technique To Glucoma Patients - Yuly Peristiowati; Hariyono; Asyafa’a Rizqi Fadilla; Putri Amanda Oktavia; Putri Nur Fadhilah; Alin Ayuning Tyas; Muhamad Hadhikul Ichwan; Marviyani Baisila; Eni Natalia Teuf; Ritalia Monika Kaka; et al. (Journal of Health Science Community, 2025)
Glaucoma is an eye disease characterized by increased intraocular pressure (IOP), which can cause pain and permanent vision loss. One non-pharmacological method that can be used to reduce pain is the Benson relaxation technique. The pain experienced by clients is influenced by a number of factors including past experiences with pain, anxiety, age, and expectations about pain relief. The first complaint of pain is felt around the eyelids and the back of the head, showing a decrease in visual acuity, then there is a halo or rainbow around the lights being seen and chemotherapies appear in the bulbar conjunctiva or edema with ciliary injection, severe corneal edema so that the cornea appears cloudy. This study aims to determine the effectiveness of the Benson relaxation technique in reducing pain intensity in glaucoma patients. The research method uses a pre-experimental design with a pre-test and post-test approach. The sample consisted of glaucoma patients who were given the Benson relaxation technique for 10-15 minutes, 1-2 times a day. The results showed a significant reduction in pain intensity after the intervention (p = 0.000, p < 0.05). This technique has been proven to be effective and can be used as a complementary nursing intervention in pain management in glaucoma patients.